Dominant News Frames, Society's Memory, and the African Asylum Seekers' Protest in Israel. (April 2018) - Tirosh, Noam
This study questions the role of media in the formation of society's memory regarding the asylum seeker struggle in Israel. Through analyzing 180 news articles published during the daily coverage of the refugees' protest in Israel between December 2013 and January 2014, this study offers an opportunity to explore the mediated environment that also shapes the refugees' situation in Israel and the role of the printed press in a memory contestation. The study demonstrates that while traditional media are a site in which different versions of the past, even including the refugees' own version, are being contested and evaluated, they are not enough to guarantee that refugees will gain recognition as such, because traditional media maintain the power to shape and construct the debate in ways that do not always support the refugees' claims.